Shedding light on minipig drug metabolism – elevated amide hydrolysis in vitro. (2nd June 2016) - Jones, Russell; Marschmann, Michaela; Keller, Michael; Qiu, Na Hong; Fowler, Stephen; Singer, Thomas; Schuler, Franz; Funk, Christoph; Schadt, Simone
Abstract: 1. In recent years, the minipig is increasingly used as a test species in non-clinical assessment of drug candidates. While there is good scientific evidence available concerning cytochrome P450-mediated metabolism in minipig, the knowledge of other metabolic pathways is more limited. 2. The aim of this study was to provide an understanding of when, why, and how drug metabolism in minipig differs from other species commonly used in non-clinical studies. In-house cross-species metabolite profile comparisons in hepatocytes and microsomes of 38 Roche development compounds were retrospectively analyzed to compare the metabolism among minipig, human, rat, dog, monkey, rabbit and mouse. 3. A significant contributor to the elevated metabolism observed for certain compounds in minipig was identified as amide hydrolysis. The hepatic amide hydrolysis activity in minipig was further investigated in subcellular liver fractions and a structure–activity relationship was established. When structural motifs according to the established SAR are excluded, coverage of major human metabolic pathways was shown to be higher in minipig than in dog, and only slightly lower than in cynomolgus monkey. 4. A strategy is presented for early identification of drug compounds which might not be suited to further investigation in minipig due to excessive hydrolytic metabolism.